Effect of occupational exposure to welding fumes and noise on heart rate variability: An exposed-unexposed study on welders and airport workers' population - Lucas, David; Guerrero, François; Jouve, Emmanuel; Hery, Sophie; Capellmann, Pascale; Mansourati, Jacques (Frontiers in Public Health, 2022)
Introduction: Welding fumes WF are a complex mixture of gas and particles. Action of occupational exposure to WF on cardiovascular system have been recently studied as for noise. Research Question: Main objectives of our study are therefore to evaluate the impact of exposure to WF, noise and combined WF and noise on ANS as assessed by Heart Rate Variabilty HRV. Methods: Ambulatory Electrocardiogram, personal WF and noise exposures monitoring respectively with Dust track and calibrated noise dosimeter were performed on 16 Welders and 8 airport workers during workday. Welders are the exposed group with noise and WF exposure and airport workers the control one. HRV parameters were summarized for all the workday and hourly. Correlation tests were used to examine relation between HRV parameters and levels of noise exposure in the two population. Analysis of Covariance ANCOVA was used for mean of each HRV parameters. Results: Mean range of High Frequencies HF, Standard Deviation of Normal to Normal R-R intervals SDNN and Root Mean Square of Successive heartbeat interval Differences RMSSD in welders were significantly higher than in airport workers. Levels of Low Frequencies LF, HF and SDNN were significantly correlated with mean noise levels for welders (respectively r = 0.62, r = 0.357, r = 0.48), not in control group. Using ANCOVA we found that working as a welder significantly increase mean of HF (p=0,01) and RMSSD (p=0,02), decrease of LF/HF (p=0,008). Interaction between exposure to WF and mean noise levels for and HF (p=0,005), LF/HF (p=0,01) and RMSSD (p=0,007). Conclusion: This study shows an impact of WF and noise on ANS balance. One hypothesis is WF exposure could increased sensibility to noise exposure on ANS or there is a synergic effect.